2020
DOI: 10.1021/acsanm.0c00932
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of a Nanoamorphous Interface Layer in B4C/Al Composites to Improve Hot Deformability and Corrosion Resistance

Abstract: In this paper, to improve the hot deformability and corrosion resistance, a nanoamorphous B 2 O 3 layer was designed and fabricated between B 4 C particles and an Al matrix successfully. The B 4 C@B 2 O 3 /Al composites were prepared by a hot-pressed sintering method. By contrast, the B 4 C/Al composites were synthesized using the same preparation method. The results show that the existence of an amorphous layer can effectively inhibit the formation of Al 3 BC, AlB 12 , and other reaction products at the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Casting is a common method for preparing AMCs. For B 4 C/Al composite, but the high B 4 C content could impair the formability during the casting process [ 116 ]. Incorporating a smaller amount of Gd instead of B 4 C has been shown to significantly enhance the plasticity and formability of AMCs while maintaining similar neutron shielding efficiency.…”
Section: Gd-containing Metallic Neutron Shielding Materialsmentioning
confidence: 99%
“…Casting is a common method for preparing AMCs. For B 4 C/Al composite, but the high B 4 C content could impair the formability during the casting process [ 116 ]. Incorporating a smaller amount of Gd instead of B 4 C has been shown to significantly enhance the plasticity and formability of AMCs while maintaining similar neutron shielding efficiency.…”
Section: Gd-containing Metallic Neutron Shielding Materialsmentioning
confidence: 99%
“…However, to increase the interfacial adhesion between BN and the polymer matrix, additional modification with coupling agents is needed [5], which might cause additional expenses. For this purpose, a B 4 C/epoxy composite was developed [6]. However, the thickness of such a coating for 80% absorption of neutron fluence was almost 9.8 mm at 3 wt% of B 4 C (particles 150µm).…”
Section: Introductionmentioning
confidence: 99%
“…Graphene 13,14 and carbon nanotubes 15,16 have excellent conductivity and can effectively improve the electrochemical performance of electrode surfaces, and consequently they have been widely employed in the fabrication of electrochemical sensors. Studies have shown that nanosized boron carbide (B 4 C), a new type of carbon-based material, [17][18][19][20] not only has a similar conductivity to graphene and carbon nanotubes, but has a large specific surface area, which means it could be expected to immobilize Cu 2 O and improve the conductivity and catalytic activity of Cu 2 O-based electrodes, thereby improving the sensitivity of the sensor.…”
Section: Introductionmentioning
confidence: 99%